Variance components and heritability estimates for first lactation traits of Sahiwal cattle by different statistical methods - RK Pundir (Journal of Livestock Biodiversity, 2025)
Variance components and heritability were estimated by Analysis of variance (ANOVA), Minimum Norm Quadratic unbiased estimates (MINQUE/MIVQUE), Maximum likelihood (ML) and Restricted Maximum Likelihood (REML) methods for age at first calving, first lactation milk yield, first lactation peak yield, First lactation length, first dry period, first service period and first calving interval from the first lactation performance records of 597 Sahiwal cows, daughters of 33 sires, spread during 1977 to 2000 and maintained at Government Livestock Farm, Hisar, India. Different methods for estimation of variance components gave similar results i.e., variance components were not statistically different by all the four methods for a particular trait as concluded by homogeneity test of variance and equality of two variances for same trait by two different methods. The moderate to high estimates of heritability for all the traits under study indicated that improvement can be made through direct selection.